Altruism in the interpretation of Russian religious philosophy - T. A. Skoropad (Дискурс)
Introduction. A number of Orthodox philosophers, among them K.N. Leontiev, criticized New  European altruism, and N.A. Berdyaev generally rejected it, calling it “the teaching of bourgeois-democratic morality, the middle-general morality of well-being, the morality of quantities”.  P.A. Florensky, N.O. Lossky, V.S. Soloviev, on the contrary, called altruism active love and  Christian agape. L.N. Tolstoy believed that the good of people lies in unity and solidarity, and  F.M. Dostoevsky called for active and selfless love, which is capable of transforming and  purifying. This position of Russian religious philosophers arouses research interest in the  author of the article. Thus, the purpose of the work is to conduct a comparative analysis of a  number of concepts of Orthodox thinkers who interpreted the concept of altruism differently,  but at the same time expressed similar opinions in relation to this ethical category. Methodology and sources. The author uses the hermeneutic method, which allows one to  immerse oneself in the study and interpretation of the texts of Russian religious  philosophers, which helps to create a voluminous hermeneutic circle of Russian culture,  highlighting its features. Results and discussions. The author's approach to the study of culture and interpretation  of cultural meanings through the analysis of ethical categories can be called original. A  similar approach may be useful to researchers in the field of cultural philosophy as a  possible method when studying a particular sociocultural system. Analyzing the concepts of  Russian religious philosophers using a similar method helps the author highlight the value  foundations of Russian culture. Conclusion. Altruism as a cultural phenomenon and ethical category, once on the soil of  Russian culture, acquires a completely different meaning and fullness.